The Tradition of Motayok Traditional Ceremonies in Cultural Heritage Management - Wibowo, Riyanto; Claudia Kheisha, Abevi; Khairune Nisa, An Nuur (Jurnal Toursci, 2024)
The traditional celebrations of Indonesia exhibit a wide range of variations, reflecting the diverse ethnic groups present in the country. One such custom is the practice of Motayok traditional rites. The Mentayok traditional ritual in cultural heritage management is rooted in the belief in supernatural forces that are believed to have the power to heal diseases and safeguard the tribe from different plagues. The ceremony follows a ritualistic musical dance, accompanied by singing, that induces a trance-like state in the dancer, allowing them to invoke spirits. This ceremony has been practiced since the 1600s. The Mokokapoi is responsible for summoning spirits while also serving as the guide during the ceremony. Typically, Mokokapoi is the spouse of the lady selected to be possessed. Totenden, as a mediator and supporter of the ritual, will join Bolian in singing the Bandit (song verses). Motayok's vocal performance and choreography will be enhanced by the rhythmic resonance of gongs and the skillful manipulation of dreadlocks by Mototobog. The Motayok traditional ceremony is seen as a form of double god or shirk. Presently, the Motayok traditional ceremony is exclusively observed in Bilalang Bersatu Village and Tudu Aog Village. There should be no necessity for the eradication of this heritage. Motayok, traditionally perceived as a mystical rite dedicated to deity veneration, is, in fact, a variant of psychotherapeutic intervention.